Strengthening and Retrofitting of Existing Structures (Building Pathology and Rehabilitation,, 2018)
This book presents the fundamentals of strengthening and retrofitting approaches, solutions and technologies for existing structures. It addresses in detail specific techniques for the strengthening of traditional constructions, reinforced concrete buildings, bridges and their foundations. Finally, it discusses issues related to standards and economic decision support tools for retrofitting. .